Metabolism of tryptophan in non-small lung cancer patients with different effect of PD-1 / PD-L1 inhibitors immunotherapy - E. Yu. Zlatnik; A. B. Sagakyants; I. A. Novikova; A. Yu. Maksimov; O. P. Shatova; S. A. Appolonova; N. E. Moskaleva; S. A. Rumyantsev; A. V. Shestopalov (Успехи молекулярной онкологии, 2022)
Introduction. In the structure of cancer incidence, lung cancer ranks first among men. In order to study the molecular mechanisms of the initiation and progression of lung cancer, it is necessary to study not only the tumor cells themselves, but also the features of the systemic tryptophan metabolism. Tryptophan catabolites, being to a large extent product of the metabolic activity of the intestinal microbiota, can affect the effectiveness of immunotherapy with checkpoint inhibitors. The kynurenine pathway of tryptophan metabolism is intensified in the body of cancer patients; its products have a pro-oncogenic and immunosuppressive effect, which may hinder the effectiveness of immunotherapy.Objective – to study the dynamics of changes in various metabolites of tryptophan metabolism in the blood serum and feces of patients with non-small cell lung cancer with various effects of immunotherapy with inhibitors of PD-1 (programmed cell death receptor 1) / PD-L1 (programmed cell death receptor 1 ligand).Materials and methods. The study included blood serum and stool samples obtained from 20 patients with non-small cell lung cancer treated with PD-1 / PD-L1 inhibitors. Using high-performance liquid chromatography with mass spectrometric analysis, the levels of 13 tryptophan metabolites were assessed in patients with various effects of immunotherapy. The significance of differences between the samples was assessed using a nonparametric method according to the Mann – Whitney test. They were considered statistically significant at p <0.05.Results. In fecal analyzes of patients in whom a positive effect of immunotherapy was observed, baseline levels of 5-hydroxyindole acetate and quinolinic acid were lower than in patients with tumor progression. Positive clinical dynamics was accompanied by a decrease in the content of indole-3-lactate, kynurenine and indole-3-carboxaldehyde in the feces of patients. In the serum of patients with a positive response, the initial content of 5-hydroxyindole acetate, indole-3-acetate, indole-3-butyrate and quinoline acid was lower than in patients with progression of non-small cell lung cancer. A positive response to immunotherapy was characterized by an increase in the levels of indole-3-butyrate and indole-3-propionate, and a negative response was not accompanied by statistically significant changes in the studied tryptophan metabolites.Conclusion. Profiling tryptophan metabolites in feces and serum of patients with non-small cell lung cancer can be used to predict the effectiveness of immunotherapy with PD-1 / PD-L1 inhibitors.